# Chain Rule of Derivatives: Statement, Formula, Proof, Examples

The chain rule of derivatives is used to find the derivative of a composite function. The rule states that the derivative of a composite function f(g(x)) is equal to f'(g(x)) ⋅ g'(x). In this post, we will learn the statement of the chain rule, its proof, step-by-step method to use this rule along with solve examples.

## Statement of Chain Rule

Let f(x) and g(x) be two functions of x. Then the derivative of the composite function f(g(x)) is computed by the chain rule and is equal to

$[f(g(x))]’ = f'(g(x)) \cdot g'(x)$.

## Proof of Chain Rule Formula

By the first principle, i.e, by definition the derivative of f(g(x)) is given by the following limit

[f(g(x))]’ = limh→0 $\dfrac{f(g(x+h)) – f(g(x))}{h}$

= limh→0 $\Big[ \dfrac{f(g(x+h)) -f(g(x))}{g(x+h)-g(x)}$ $\times \dfrac{g(x+h) – g(x)}{h} \Big]$

= limh→0 $\dfrac{f(g(x+h)) -f(g(x))}{g(x+h)-g(x)}$ × limh→0$\dfrac{g(x+h) – g(x)}{h}$

= f'(g(x)) ⋅ g'(x), obtained by the definition of derivatives at a point.

Thus, we have shown that [f(g(x))]’ = f'(g(x)) ⋅ g'(x) and this is the chain rule of derivatives. ♣

## Chain Rule Step-by-Step

The following steps are used in order to find the derivative of a composite function y(x) using chain rule:

Step 1: First check that y(x) is a composite function or not.

Step 2: If y(x) is composite, then it can be written as f(g(x)) where g(x) is the inner function and f(x) is the outer function.

Step 3: Now, determine the inner and outer functions.

Step 4: Find the derivatives of the inner and outer functions.

Step 5: Compute f'(g(x)) ⋅ g'(x).

Step 6: Simplify the above product.

Step 7: The simplification in the previous step is the derivative of the composite function y(x) =f(g(x)).

Before we provide examples on how to find the derivatives by chain rule, let us recall its formula.

## Solved Examples on Chain Rule

Let us find the derivative of e3x by the chain rule as it is a composite function. Note that we can write it as

f(g(x)) where g(x)=3x and f(x)=ex.

Let u=3x. So du/dx =3.

Now, by the chain rule,

d/dx (e3x)

= d/du (eu) ⋅ du/dx

= eu ⋅ 3

= 3e3x as u=3x.

So the derivative of e3x by the chain rule is 3e3x.

Note that sin(2x) can be written as f(g(x)) where g(x)=2x and f(x)=sin(x).

Put u=2x. So du/dx =2.

By the chain rule of derivatives,

d/dx (sin2x)

= d/du (sin u) ⋅ du/dx

= cos(u) ⋅ 2 since the derivative of sinx is cosx.

= 2cos(2x) as u=2x.

So the derivative of sin(2x) by the chain rule is 2cos(2x).

## FAQs on Chain Rule

Q1: What is Chain Rule in Derivatives?

Answer: Chain rule is used to find the derivative of a composite function, and it says that the derivative of f(g(x)) is equal to f'(g(x)) ⋅ g'(x). For example, sin(2x) is a composite function and we write it as f(g(x)) where f(x)=sin(x) and g(x)=2x. So by the chain rule, the derivative of sin(2x) is 2cos(2x).

Share via: